ANALISIS PENGARUH KREDIT USAHA RAKYAT (KUR) TERHADAP PENINGKATAN PINJAMAN PADA PT. BANK RAKYAT INDONESIA TBK. UNIT BORONGLOE KABUPATEN GOWA - Dirwan Dirwan (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2013)
This study aimed to determine the effect of interest rates, collateral, and term of the loan increasing. Analysis tools are used in research quantitative analysis (validity and reliability), multiple regression analysis, t test, f test and the coefficient of determination. The population in this study are all debtors who have taken small loans at PT Bank Rakyat Indonesia Tbk, Unit Borongloe Romanglompoa Gowa district. In this study, 96 respondents in the sample. Determination of the sample using the formula Slovin. From the results of multiple regression analysis obtained regression equation Y = 0.621 + 0.294 + 0.364X1 0.252 X2 + X3. This means that the variable interest rate, collateral and term positive effect on growth in lending. While testing the hypothesis derived from the t value for the interest rate (X1) of 3.930 with a significance level of 0.000, to guarantee (X2) t count equal to 2.786 with a significance level of 0.006 and t count variable period of 2.663 with a significance level of 0.009. Thus means that the results of the t test analysis stated significant results for all variables and the hypothesis is accepted. The results of multiple regression analysis also shows the value of the coefficient of determination equal to 0.667, which means the variable interest rate, collateral and loan term affects the increase of 66.7%, while 33.3% is influenced by other variables that are not observed in this study.